DISKRIMINASI GENDER DI MEDIA TELEVISI - Nursalim Nursalim (Marwah: Jurnal Perempuan, Agama dan Jender, 2011)
This article studies how woman presented to society on television. In relation to masculine and feminine, television always descripts woman as a domestic person which depend on the power of men. Vice versa, a man is a public person who does not depent on the power of woman. Also the senetron theme presents the relation of masculine and feminine where man always comes up as a person who has capability to protects the woman which considered as the person who does not has capability. Therefore, the changes to the various televison programms has to be done absolutely by various side which bother about the existence of gender justice in the public area.